2008
DOI: 10.1086/588476
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lactoferrin Supplementation on Growth and Prevalence ofGiardiaColonization in Children

Abstract: We conducted a randomized, double-blind, placebo-controlled trial comparing supplementation with bovine lactoferrin versus placebo for the prevention of diarrhea in children. Comparison of overall diarrhea incidence and prevalence rates found no significant difference between the 2 groups. However, there was a lower prevalence of colonization with Giardia species and better growth among children in the lactoferrin group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 11 publications
3
47
0
2
Order By: Relevance
“…Tests carried out on mandarins with bLfcin and Lf (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) showed a significant protection against Penicillium digitatum at a concentration close to the in vitro MIC value [115]. More recently Baruzzi et al demonstrated the interesting activity of bLfcin in controlling microbial spoilage in ready-to-eat leafy vegetables during cold storage [116].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Tests carried out on mandarins with bLfcin and Lf (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) showed a significant protection against Penicillium digitatum at a concentration close to the in vitro MIC value [115]. More recently Baruzzi et al demonstrated the interesting activity of bLfcin in controlling microbial spoilage in ready-to-eat leafy vegetables during cold storage [116].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…We recently conducted a small community-based randomized double blind placebo controlled trial comparing twice daily oral supplementation with bovine lactoferrin (10−20% iron saturated, 1 g/day) (Tatua Cooperative Dairy Co, Morrinsville, New Zealand) versus placebo for 9 months in 52 Peruvian children 12−36 months of age [54]. Despite the small number of children enrolled in this study, several potentially useful observations were made related to bovine lactoferrin supplementation.…”
Section: Clinical Studies Of Lactoferrin's Effect On Enteric Pathogensmentioning
confidence: 99%
“…Safety relevant endpoints were not studied. In two studies in Peruvian children which reported on adverse events the number of adverse events did not differ between the treatment and the placebo group and no adverse event could be attributed to the test substance (Ochoa et al, 2008;Zavaleta et al, 2007).…”
Section: Studies In Childrenmentioning
confidence: 93%
“…Four published studies with a duration of fifteen days to nine months investigated presumed antimicrobial effects of bLF at intakes between 100 and 1,000 mg per day alone or in coadministration with other substances (Ajello et al, 2002;Egashira et al, 2007;Ochoa et al, 2008;Zavaleta et al, 2007). Safety relevant endpoints were not studied.…”
Section: Studies In Childrenmentioning
confidence: 99%